MGH Cardiology Board Review - Gaggin, Hanna K.; Gaggin, Hanna K.; Januzzi, Jr., James L.; Januzzi, Jr., James L. (Springer London : Imprint: Springer, 2014)
Preparing for the cardiology board examination is an intensely stressful period and traditionally relies on the participant searching through their own references, whether that be the large textbooks, small handbooks and their own notes.  Good books are generally too long and time-consuming, while shorter books are either insubstantial in content or rely too much on the views of one author. The key elements for a successful reference for those taking their boards are a balanced proportion of essential content alongside rare but frequently tested topics, the wisdom of experts in the field, a practical questions session at the end of every topic and additional visuals not possible on the two-dimensional page.  In the MGH Cardiology Board Review, the Editors have compiled the expertise of over 72 experienced authors from the Mass General in a succinct volume, applying methods thoroughly tested in the Board Review Conference.  In addition, two very important sections are included on ECGs and images, contents of which are derived from the board examination answer keys, the very ones that readers are expected to know.  Plans on how to best approach the board examination preparation and what additional resources to go to are provided.  In short, this book has all the strengths to ensure your success on the boards exam.   .